2013
DOI: 10.1002/eat.22201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of children and adolescents referred for eating disorder treatment at a specialist tertiary setting

Abstract: The clinical presentation of EDs differs among children and adolescents, with eating pathology and behavioral symptoms less prominent among children. Frontline health professionals require knowledge of these differences to assist with early detection, diagnosis, and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 50 publications
2
37
3
1
Order By: Relevance
“…Researchers have pointed out that the clinical presentation of children with ED differs substantially from that of adolescent and adult patients in the following aspects: shorter disease duration, fewer symptoms of ED, lower frequency of binge/purge and physical exercises to control weight, faster loss of weight, and increased risk of growth problems 9,11 .…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have pointed out that the clinical presentation of children with ED differs substantially from that of adolescent and adult patients in the following aspects: shorter disease duration, fewer symptoms of ED, lower frequency of binge/purge and physical exercises to control weight, faster loss of weight, and increased risk of growth problems 9,11 .…”
Section: Resultsmentioning
confidence: 99%
“…These include pressures experienced by younger patients, such as changes related to puberty and external negative in uences on body image perception and idealisation (38). It has been postulated that onset of AN prior to puberty may intensify perceived body image ideals (39), whereby the associated increase in adipose tissue and widening of the hips in adolescent females during puberty may exacerbate cognitions related to thin body ideal (13). Moreover, experience of body change in the EO-AN group may also be substantially in uenced by social media ideals, peer relationships and the emergence of gender roles (40,41) which may also contribute to the heightened stress and anxiety seen in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations into AOO in AN are inconclusive, with con icting evidence surrounding the impact of AOO on ED severity, prognostic implications and psychological pro le. Evidence for increased ED severity and poorer prognostic outcomes in EO-AN (as compared to LO-AN) have been demonstrated including; more rapid weight loss (12,13), poorer long-term outcomes of low body weight and psychiatric comorbidity (14), and a longer duration of illness (15). However, other studies have found no difference in severity of weight loss between EO-and LO-AN (16), fewer cases of extremely low weight in those with EO-AN compared to LO-AN (17), and a positive association between low body mass index (BMI) and increased AOO (18).…”
mentioning
confidence: 99%
“…All the children and adolescents need eating disorder treatment [3]. They need an negativebalance between energy intake (low-calorie, nutrient-dense foods) and energy output (physical activity and exercise).…”
Section: The Causes Of Obesitymentioning
confidence: 99%